2001
DOI: 10.3406/bspf.2001.12483
|View full text |Cite
|
Sign up to set email alerts
|

Le Châtelperronien de la grotte du Renne à Arcy-sur-Cure (Yonne). Données sédimentologiques et chronostratigraphiques

Abstract: La grotte du Renne à Arcy-sur-Cure est l'un des gisements les plus importants pour la transition Paléolithique moyen/supérieur mais sa position chronologique n 'est pas encore bien établie. Une coupe a donc été rouverte en 1998 pour reprendre des échantillons pour datation. Dans la perspective de la publication des données châtelperroniennes des fouilles Leroi- Gourhan, elle a permis de compléter les informations stratigraphiques et sédimentologiques de la couche X et de montrer la cohérence du dépôt. Un aperç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 2 publications
1
13
0
2
Order By: Relevance
“…This suggests that some material is probably derived from the lower Mousterian levels. This could have occurred when the first Châtelperronian occupation began, as suggested previously (15). There is evidence for digging and leveling at the site during this period.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This suggests that some material is probably derived from the lower Mousterian levels. This could have occurred when the first Châtelperronian occupation began, as suggested previously (15). There is evidence for digging and leveling at the site during this period.…”
Section: Discussionsupporting
confidence: 56%
“…has resulted in a wide range of ages covering 28,000-45,000 B.P., with little stratigraphic consistency (ref. 15, Fig. S1, and Tables S1 and S2).…”
mentioning
confidence: 99%
“…Until the late 1990s, attempts at radiocarbon dating the Grotte du Renne sequence yielded results for the Châtelperronian falling for the most part in the 32-34 ka 14 C BP age range (David et al 2001 ), supporting the interstratifi caton arguments for long-term contemporaneity with the Aurignacian and thereby strengthening Acculturation views of the evidence. The numerous inconsistencies in the dating corpus, however, indicated that those results, obtained on associated animal bone samples, were likely to be minimum ages only, while detailed analysis of the stone tool assemblage in level VII eventually allowed its assignation to the Protoaurignacian (Bon 2002 ;Bon and Bodu 2002 ).…”
Section: Grotte Du Rennementioning
confidence: 81%
“…S3). In layer X, occupation floors (sublayers) were tentatively identified and numbered (27). However, their identification and recognition was not always straightforward and several artifact refits were detected between the sublayers of X (28) (Fig.…”
Section: Grotte Du Renne Stratigraphymentioning
confidence: 99%